OFR-48-79 Design And Fabrication Of Instrumentation For Remote Sealing Of Underground Coal Mine Passageways - Volume I - David A. Monaghan (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report describes instrumentation which is part of a system for extinguishing mine fires by pumping material through surface boreholes in order to seal off all underground passageways leading to the fire area. Major instrumentation systems include a closed circuit television probing system and an acoustic seal checking system. The latter consists of a speaker probe, a receiver probe and related signal processing equipment. All probes can be winch-deployed down a 6-inch diameter borehole. The CCTV unit can be rotated 360 degrees in the horizontal plane, and contains sufficient lighting to reliably assay conditions for sealing or rescue within a 200 foot radius. The acoustic seal checker monitors the completion of a seal as it progresses by use of probes lowered through boreholes on either side of the seal.